USING FORTIFICATION FOODS INTERVENTION FOR WOMEN AND CHILDREN IRON DEFICIENCY ANEMIA: A SCOPING REVIEW - Lilik Hidayanti (Faculty of Public Health, Andalas University, 2019)
Women and children are at risk of suffering iron deficiency anemia. The scoping reviews were aimed to examine experimental research articles that were published last than 10 years ago or from 2008. The searching articles results through 11 electronic search engines (Medline, CINAHL, PubMed, etc.) found 668 articles. After the screening process based on the specified inclusion criteria, 51 articles will be examined. The result of articles review that we had done showed 35 articles had positive impact after they were given an intervention with fe fortification in various types of food for all subjects. However, there were still 16 articles that showed no significant changes after being given an intervention. This review of the studies still required statistical analysis of the data found to provide a better results